Economic mechanism of ensuring products competitiveness of the region’s food industry (Journal of Economic Research & Business Administration, 2018)
The article considers the features of the regional food industry, its advantages and disadvantages,and ways to increase its competitiveness. In the era of the market, the role of competitiveness in theindustry is defined, theories and concepts appear. The modern technologies and opportunities of theregion in the sphere of increasing the competitiveness of the food industry are considered, the main disadvantagesof the industry are determined. The definition of the concept of competition is also provided.The author used known statistical data and analyzes of basic theories and tried to analyze these datain order to improve and deepen the article. The basic definitions of the economy and competitivenessof regional industry in modern conditions are given. The works of Russian and foreign authors on thissubject have been studied and analyzed by the author. The relevance and significance of the article isopen, clear. It is worth paying attention to the fact that the author reveals the theory of cooperatives andthe theory of a regional cluster. The article is intended for people who are interested in the developmentof regional industry, marketing, public relations and advertising.